The Impact of Civil Law Outreach on Public Understanding of Land and Inheritance Disputes in the Jakarta Capital Region - Gunawan Widjaja (Bulletin of Community Engagement, 2026)
This study aims to analyse the impact of civil law outreach programmes on the public’s understanding of land and inheritance disputes in the DKI Jakarta region. The research method employed a literature review using a qualitative-descriptive approach to analyse various sources of literature relevant to the research context. The results of the study indicate that civil law education has a significant positive impact on improving the understanding of the public in DKI Jakarta regarding land and inheritance disputes, particularly concerning the legality of land certificates, procedures for sale, purchase and transfer of ownership, the distribution of inheritance according to the Civil Code and the Islamic Inheritance Law, as well as the importance of legal documents such as wills and deeds of inheritance. This improved understanding contributes to increased legal awareness among the public regarding the legal processing of land certification and the transfer of rights, as well as orderliness in the recording of inheritance, which ultimately reduces family conflicts. Nevertheless, there are various obstacles, such as a limited number of legal educators, the diversity of the public’s educational backgrounds, legal language that is too technical, a cultural perception that discussing inheritance is taboo, and limitations in the timing and location of the legal education sessions. This study recommends the need for synergy between the government, legal aid institutions, religious leaders, traditional leaders, and the community, adopting a more holistic and sustainable approach through training for village officials, the development of more comprehensive materials, the use of digital media, and regular evaluations to enhance the effectiveness of civil law outreach in reducing land and inheritance disputes in Jakarta.